Building for Peace : Reconstruction for Security, Equity, and Sustainable Peace in MENA - World Bank (World Bank, Washington, DC, 2020)
Tragic levels of death, destruction, displacement, and disorder from ongoing conflicts in Iraq, Libya, Syria, and Yemen require a new approach focused on building – not rebuilding – to support transitions to sustainable peace. This is the key message of this new World Bank report funded by the German Federal Ministry for Economic Cooperation and Development (BMZ). Building for Peace combines the latest development thinking with original research and proposes an integrated approach to look at reconstruction, development, and the transition to sustainable peace for conflict countries in the Middle East and North Africa and globally. It argues that, because the nature of conflict has evolved, the ways of planning and prioritizing interventions should also evolve, as must the ways that governments, development actors, and donors engage in those environments. Building for Peace advocates a more bottom-up approach that complements the approaches centered on physical reconstruction and central government institutions and that links past, present, and future. It suggests starting by understanding the past and the factors that led to conflict and by making sense of the present by identifying the power and incentives of existing actors, the existing allocation of resources, and the political and economic interests revolving around war. This more nuanced and holistic analysis helps to map the future by developing a long-term vision for sustainable peace. That vision is anchored on the priorities of the communities affected and the associated risks, constraints, and tradeoffs. It also addresses past grievances by building on existing assets and not just on physical damage—and by focusing on creating economic opportunities for all people affected by the conflict.